Multi-instrumental investigation of the solar flares impact on the ionosphere on 05–06 December 2006 - Barta, Veronika; Natras, Randa; Srećković, Vladimir; Koronczay, David; Schmidt, Michael; Šulic, Desanka (Frontiers in Environmental Science, 2022)
The sudden increase of X-radiation and EUV emission following solar flares causes additional ionization and increased absorption of electromagnetic (EM) waves in the Earth’s atmosphere. The solar flare impact on the ionosphere above Europe on 05 and 06 December 2006 was investigated using ground-based (ionosonde and VLF) and satellite-based data (Vertical Total Electron Content (VTEC) derived from GNSS observations and VLF measurements from DEMETER satellite). Based on the Kp and Dst indices, 05 December was a quiet day, while there was a geomagnetic storm on 06 December 2006. The total fade-out of the EM waves emitted by the ionosondes was experienced at all investigated stations during an X9 class flare on 05 December. The variation of the fmin parameter (first echo trace observed on ionograms, it is a rough measure of the “nondeviative” absorption) and its difference between the quiet period and during the flares have been analyzed. A latitude dependent enhancement of fmin (2-9 MHz) and Deltafmin (relative change of about 150-300 %) was observed at every station at the time of the X9 (on 05 December) and M6 (on 06 December) flares. Furthermore, we analyzed VTEC changes during and after the flare events with respect to the mean VTEC values of reference quiet days. During the X9 solar flare, VTEC increased depending on the latitude (2-3 TECU and 5-20 %). On 06 December, the geomagnetic storm increased ionization (5-10 TECU) representing a „positive” ionospheric storm. However, an additional peak in VTEC related to the M6 flare could not be detected. We have also observed a quantifiable change in transionospheric VLF absorption of signals from ground transmitters detected in low Earth orbit associated with the X9 and M6 flare events on 05 and 06 December in the DEMETER data. Moreover, amplitude and phase of ground-based, subionospherically propagating VLF signals were measured simultaneously during the investigated flares to analyze ionosphere reaction and to evaluate the electron density profile versus altitude. For the X9 and M6 flare events we have also calculated the ionospheric parameters (sharpness, reflection height) important for the description and modelling of this medium under forced additional ionization.